MENINGKATKAN KEPUTUSAN PEMBELIAN MELALUI KUALITAS PELAYANAN DAN PROMOSI PENJUALAN - Aang Curatman; Soesanty Maulany; Shofiullah Shofiullah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
The purpose of this study is to analyze the effect of service quality and sales promotion on consumer purchasing decisions at E Sport Cirebon Shop, either partially or simultaneously. The population of this research is consumers of E Sport Cirebon stores with unknown population, while the sample is 96 respondents. The sampling technique used non-probability sampling using incidental sampling. This research is an associative type with quantitative methods. Based on the T test it is known that service quality and sales promotion have a partial effect on purchasing decisions, as well as based on the F test it is known that service quality and sales promotion have a simultaneous influence on purchasing decisions. Therefore the company should improve service quality and provide variations in the types of sales promotions to improve consumer purchasing decisions.